Biotic Evolution and Environmental Change in Southeast Asia (2012)
Southeast Asia has long been of major interest for many scientific disciplines, both separetely and in the way the different disciplines have interacted with each other in trying to address the numerous different groups of organisms. Moreover, this high diversity is true througt a large range of enviroments,aquatic to terretrial, and freswater to marine.